ANALISIS HUBUNGAN ANTARA PENGETAHUAN TENTANG KESELAMATAN KESEHATAN KERJA (K3) DAN PERILAKU PENGGUNA ALAT PELINDUNG DIRI (APD) DENGAN DOSIS RADIASI PEKERJA - Riyanto -; Charles Situmorang; Deni Kurniawan (JURNAL TECHLINK, 2022)
This study aims to analyze the relationship between knowledge about occupational health safety (OHS) and the behavior of users of personal protective equipment (PPE) with the radiation dose of workers. The research method used is quantitative. The population of this research is all radiation workers, totaling 12 workers at PT Incoray Nitrama. The sampling technique is a saturated sample, that is, all members of the population are used as samples. The research sample consisted of 12 radiation workers. Data analysis used simultaneous correlation regression, t test, and coefficient of determination. The results showed that, there was a negative and significant relationship between knowledge of OHS and behavior of PPE users together on radiation worker doses, because it was in the range of Fcount 6.043 > Ftable 4.26 at = 0.05. That is, the higher the knowledge of K3 and the behavior of PPE users, the lower the dose of radiation workers will be exposed to. The conclusion of the study, if exposure to radiation dose of workers is low, then factors such as knowledge of OHS and behavior of PPE users are increased. The coefficient of determination of OHS knowledge and behavior of PPE users together on radiation worker dose (R Square) is 0.573. This shows that 57.3% of the variance in radiation worker doses can be explained by knowledge of OHS and behavior of PPE users together, the remaining 42.7% is influenced by other factors outside the variables studied.